Study of surface condition of Bi2212 bismuth-based cuprate sample by chemical imaging method (Eurasian Journal of Physics,Chemistry and Mathematics, 2024)
In the article, during the synthesis of the Bi-2212 cuprate sample, the change of the surface state of the sample under the influence of heat, the surface state of the sample after sintering was studied using the chemical imaging method. The irregularities on the surface of the sample were monitored and their dependence on the sintering temperature was studied. As a research object, we synthesized cuprate based on the formula Bi2+ySr2-yCaCu2O8+x and studied its properties. Assessment of sample condition by chemical imaging is an important factor for all types of cuprates